Effect of Tank Geometry on Its Average Performance - Orlov A. A. Aleksey Alekseevich; Tsimbalyuk A. F. Aleksandr Fedorovich; Malyugin R. V. Roman Vladislavovich; Leontieva D. A. Daria; Kotelnikova A. A. Alexandra (2018, 2018)
Title screen